Cinder house - Marske, Freya (Tordotcom/Tor Publishing Group, 2025)
"Sparks fly and lovers dance in this gorgeous, yearning Cinderella retelling from bestselling author Freya Marske-a queer Gothic romance perfect for fans of Naomi Novik and T. Kingfisher. Ella is a haunting. Murdered at sixteen, her ghost is furiously trapped in her father's house, invisible to everyone except her stepmother and stepsisters. Even when she discovers how to untether herself from her prison, there are limits. She cannot be seen or heard by the living people who surround her. Her family must never learn she is able to leave. And at the stroke of every midnight, she finds herself back on the staircase where she died. Until she forges a wary friendship with a fairy charm-seller, and makes a bargain for three nights of almost-living freedom. Freedom that means she can finally be seen. Danced with. Touched. You think you know Ella's story: the ball, the magical shoes, the handsome prince. You're halfway right, and all-the-way wrong. Rediscover a classic fairy tale in this debut novella from "the queen of romantic fantasy" (Polygon)"-- Provided by publisher.